Performance Appraisal And Situational Leadership Style In Influencing Employee Performance Through Job Satisfaction At Inden Indonesia Ltd. - Fitri Rezeki; Ni Desak Made Santi Diwyarthi Made Santi Diwyarthi (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Employee performance problems are fundamental for companies to achieve their business goals. This study aims to measure how much impact is influenced by performance appraisal and leadership style on employee performance with the role of job satisfaction mediation. This study uses the principle of explanatory research to test 99 respondents and the influence between variables in a structural model that seeks to test the influence of dependent variables on independent variables. The analysis method in this study uses a structural analysis approach where the processing uses PLS software. This study consists of two exogen variables, namely Work Assessment and Situational Leadership Style, two endogenous variables consisting of one Mediation variable, namely Job Satisfaction, and one dependent variable, Employee Performance. The data source used in this study used primary data. The data collection process was carried out to get input from respondents who became research samples per the design and research variables. This research results in a positive influence directly and indirectly on employee performance. Job satisfaction also has a positive impact on influencing employee performance. The study found that leadership style cannot affect employee performance but can be improved by the role of job satisfaction.